Gamification in Islamic Religious Education for Primary Students: A Systematic Review on Motivation, Emotional Engagement, and Learning Psychology - M. Al Ravi Azis; Koko Adya Winata; Laesti Nurishlah; Syifa Rohmati Mashfufah; Romi Wilza (Proceeding of the International Conference on Social Sciences and Humanities Innovation, 2025)
This article delves into the application of gamification in Islamic Religious Education (IRE) for primary school students, focusing on its impact on motivation, emotional engagement, and learning psychology. It offers a systematic review of relevant studies, evaluating both the positive outcomes and challenges of using gamification in IRE. A thorough library research approach was used, drawing from academic journals, books, and conference papers. Key databases like Google Scholar, JSTOR, and ERIC were searched to identify studies published between 2010 and 2025. Studies that met specific criteria relevance to the topic, educational level, and a focus on gamification, motivation, emotional engagement, and learning psychology were selected. The findings suggest that gamification in IRE can significantly enhance student motivation, emotional engagement, and learning outcomes. Elements such as rewards, challenges, and interactive activities help create a positive learning environment, promoting better retention and understanding of Islamic teachings. Emotional engagement is particularly heightened when gamification is tailored to the cultural and religious contexts of the students, fostering a deeper connection to the material. The study emphasizes that incorporating gamification in IRE could enhance the overall educational experience for primary students, boosting their motivation and emotional involvement in learning. It also highlights the importance of designing gamified content that is culturally relevant and contextually appropriate to maximize the positive effects on student learning. The study recommends that educators, curriculum developers, and policymakers consider using gamification to improve the quality of Islamic education in primary schools.